Regulatory control analysis and design for sewer systems. (April 2015) - Mollerup, Ane Loft; Mikkelsen, Peter Steen; Thornberg, Dines; Sin, Gürkan
Abstract: A systematic methodology for regulatory control analysis and design is adapted for sewer system operation and evaluated. The main challenge with adapting the methodology is the handling of the stochastic and transient nature of the rainfall disturbances, inherent to sewer system operation. To this end, four distinct modes of operation are identified (dry weather, filling, saturation and emptying) and for each of these the process gain matrix is found. Based on the gain matrices a controllability analysis is performed, to screen for suitable pairings between measurements and actuators in the case study area of Copenhagen. The analysis effectively reduces the number of potential controlled variables, by considering the sensitivity of the measurements towards changes in the manipulated variables. Several potential pairings are generated and the best alternative is chosen for closed-loop testing. The methodology is a promising tool for systematic generation of solutions for sewer system control. Highlights: A systematic methodology for regulatory control design is adapted to sewer systems. The main challenge in control analysis is handling the transient dynamics. Transfer function matrix models identified four operation modes of the sewer system. Using controllability analysis three independent control loops was generated. The design of the regulatory control was confirmed using 10 years of rain data.